Evaluasi Kebijakan Calon Tunggal dalam Pemilihan Kepala Daerah Tahun 2024 di Kabupaten Bangka - Siti Aminah; Yan Megawandi; Sena Putra Prabujaya; Darol Arkum (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
This study aims to evaluate the implementation of the single-candidate policy in the 2024 Regional Head Election (Pilkada) in Bangka Regency and analyze its impacts on political, economic, and social dynamics within the community. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. Policy evaluation was carried out using William N. Dunn’s policy evaluation criteria, which include effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that procedurally the single-candidate policy ensures the continuity of the regional election process in accordance with existing regulations. However, substantively the policy still faces several limitations, particularly in fostering healthy political competition and fulfilling public expectations for a more representative democratic process. Furthermore, the single-candidate phenomenon also affects political participation, regional financial burdens, and broader social dynamics within the local democratic system.